INHIBITION OF MICROSOMAL LIPID PEROXIDATION AND PROTEIN OXIDATION BY EXTRACTS FROM PLANTS USED IN BAMUN FOLK MEDICINE (CAMEROON) AGAINST HEPATITIS - Njayou, Frederic N; Moundipa, Paul F; Tchana, Angele N; Ngatjui, Bonaventure T.; Tchouanguep, Felicite M. (African Journal of Traditional, Complementary and Alternative Medicines, 2008)
The antioxidant activities of 53 medicinal plants used in Bamun Folk Medicine for the management of jaundice and hepatitis were investigated. The studies were done using rat hepatic microsomes for lipid peroxidation and bovine serum albumin (BSA) for carbonyl group formation. Silymarine was used as reference compound. Fifteen different extracts were effective at a dose of 200µg/ml in both experiments. Specifically, 25 extracts inhibited lipid peroxidation initiated non-enzymatically by ascorbic acid while 18 inhibited peroxidation as determined by reduced Nicotinamide Adenine Dinucleotide Phosphate (NADPH). The inhibitory concentration 50 (IC50) of 23 different plant extracts was lower than 200µg/ml in the microsomal lipid peroxidation inhibition study. Fifteen of the 23 extracts were active in preventing protein oxidation by inhibiting the formation of the carbonyl group on BSA with an IC50 value less than 200µg/ ml. The results suggest that the antioxidant activity of the extracts, may be due to their ability to scavenge free radicals involved in microsomal lipid peroxidation or in protein oxidation. These biochemical processes are involved in the aetiology of toxic hepatitis.